2022
DOI: 10.1186/s12884-022-04807-8
|View full text |Cite
|
Sign up to set email alerts
|

The trend in delayed childbearing and its potential consequences on pregnancy outcomes: a single center 9-years retrospective cohort study in Hubei, China

Abstract: Background Due to the advancement of modern societies, the proportion of women who delay childbearing until or beyond 30 years has dramatically increased in the last three decades and has been linked with adverse maternal-neonatal outcomes. Objective To determine the trend in delayed childbearing and its negative impact on pregnancy outcomes. Material and methods A tertiary hospital-based retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…A study in Hubei, China, found that the trend of advanced maternal age (age ≥35) increased by 75% from 2011 to 2019, and noted that advanced maternal age was associated with an increased risk of pre-eclampsia (OR=1.6) and GDM (OR=2.5) after adjusting for confounding factors. 29 Shan et al found that the risk of pre-eclampsia increased dramatically with maternal age. In addition, older pregnant women have a twofold to threefold risk of being diagnosed with GDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Hubei, China, found that the trend of advanced maternal age (age ≥35) increased by 75% from 2011 to 2019, and noted that advanced maternal age was associated with an increased risk of pre-eclampsia (OR=1.6) and GDM (OR=2.5) after adjusting for confounding factors. 29 Shan et al found that the risk of pre-eclampsia increased dramatically with maternal age. In addition, older pregnant women have a twofold to threefold risk of being diagnosed with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…In different racial and ethnic groups, many epidemiological studies have reported positive associations between advanced maternal age and pre-eclampsia and GDM, which was consistent with our findings. A study in Hubei, China, found that the trend of advanced maternal age (age ≥35) increased by 75% from 2011 to 2019, and noted that advanced maternal age was associated with an increased risk of pre-eclampsia (OR=1.6) and GDM (OR=2.5) after adjusting for confounding factors 29. Shan et al found that the risk of pre-eclampsia increased dramatically with maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a concordant decrease in oocyte quality which is associated with increased infertility and miscarriage rates (Broekmans et al, 2009). The shift to delayed childbearing in recent decades is associated with adverse fertility and maternal‐neonatal outcomes including chromosomal abnormalities, birth defects, increased risk of morbidity and mortality, high risk of cesarean delivery, preeclampsia, and postpartum hemorrhage (Aoyama et al, 2019; Hook, 1981; Li et al, 2022; Sauer, 2015; Sheen et al, 2018). Therefore, understanding the mechanisms of female reproductive aging is key to establishing new strategies to extend ovarian reproductive and endocrinological longevity and to improve infertility treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, it has also been presumed to be due to the trend of late marriage accompanying women's social advancement and the development of assisted reproductive technology (ART) [4]. However, AMA, especially for ages over 40, has been reported to be an independent risk factor for adverse obstetric outcomes [1,[5][6][7][8]. Most studies have agreed that AMA is related to an increase of adverse maternal and fetal outcomes such as preeclampsia, fetal growth restriction, prematurity, and cesarean delivery [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, AMA, especially for ages over 40, has been reported to be an independent risk factor for adverse obstetric outcomes [1,[5][6][7][8]. Most studies have agreed that AMA is related to an increase of adverse maternal and fetal outcomes such as preeclampsia, fetal growth restriction, prematurity, and cesarean delivery [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%